2015
DOI: 10.1007/s00384-015-2460-y
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cancer with complete clinical response after neoadjuvant chemoradiotherapy, surgery, or “watch and wait”

Abstract: A watch and wait policy avoids the morbidity associated with radical surgery and preserves oncologic outcomes in our retrospective study from a single institute. It could be considered a therapeutic option in patients with locally advanced rectal cancer following chemoradiotherapy with a complete clinical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 23 publications
2
55
0
4
Order By: Relevance
“…1327 Eight studies reported data for an adequate control proctectomy group, but there was significant variation. Four used a post-surgical pathological complete response (pCR) group for comparison 14,16,25,26 , 2 used cCR tumors undergoing surgery, 19,20 1 used both, 22 and 1 used a surgical group matched for clinical stage (regardless of tumor response). 23 Outcome data for incomplete response, non-response, and local excision were excluded from comparisons as these were not regarded as adequate control group data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1327 Eight studies reported data for an adequate control proctectomy group, but there was significant variation. Four used a post-surgical pathological complete response (pCR) group for comparison 14,16,25,26 , 2 used cCR tumors undergoing surgery, 19,20 1 used both, 22 and 1 used a surgical group matched for clinical stage (regardless of tumor response). 23 Outcome data for incomplete response, non-response, and local excision were excluded from comparisons as these were not regarded as adequate control group data.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the use of consolidation or adjuvant chemotherapy was highly variable, ranging from frequent use, 18,25,26 to use only if staged as node positive prior to neoadjuvant treatment, 15,21 infrequent use, 14,20,23 and complete omission. 13,16,17,19,22 Consolidation or adjuvant chemotherapy, when used, was most commonly 5-FU based with the addition of Oxaliplatin in two studies. 21,25 …”
Section: Resultsmentioning
confidence: 99%
“…This has notably improved survival and made minimally-invasive treatments more feasible. Neo-adjuvant chemo radiotherapy (CRT), followed by total mesorectal excision (TME) and adjuvant chemotherapy, remains the gold standard in the treatment of locally advanced rectal cancer (LARC) (4). LARC generally refers to Stage III rectal cancer, and it represents 70% of the rectal cancers on presentation (5).…”
mentioning
confidence: 99%
“…Results of other retrospective studies of the watch-and-wait approach from the US, 22 UK, 23 and Taiwan, 24 together with the Brazilian studies, [19][20][21] are summarised in Table 1. They are all single-centre studies and include a small number of patients.…”
Section: Retrospective Studiesmentioning
confidence: 99%